2014
DOI: 10.1002/hep.27079
|View full text |Cite
|
Sign up to set email alerts
|

Prediagnostic circulating vitamin D levels and risk of hepatocellular carcinoma in European populations: A nested case-control study

Abstract: The association between vitamin D status and hepatocellular carcinoma (HCC) has not been well investigated, despite experimental evidence supporting an important role of vitamin D in liver pathophysiology. Our objective was to investigate the association between prediagnostic circulating 25-hydroxyvitamin D [25(OH)D] serum levels and the risk of HCC in a prospective, nested case-control study among 520,000 participants in the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort. Each case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
70
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 47 publications
(75 reference statements)
8
70
0
1
Order By: Relevance
“…In vitro és in vivo vizsgálatok zajlanak a számos terápiás próbálkozás ellenére is igen rossz prognózisú hepatocellularis carcinoma carcinogenesisében betöltött szerepéről és esetleges terápiás alkalmazásáról [17,22,23]. Vita tárgyát képezi az alacsonyabb szérum-1,25-dihidroxi-D 3 -vitamin-szint és a hepatocellularis carcinoma kialakulásának magasabb kockázata között fennálló ösz-szefüggés [24,25]. Huang és munkacsoportja a közel-…”
Section: Megbeszélésunclassified
“…In vitro és in vivo vizsgálatok zajlanak a számos terápiás próbálkozás ellenére is igen rossz prognózisú hepatocellularis carcinoma carcinogenesisében betöltött szerepéről és esetleges terápiás alkalmazásáról [17,22,23]. Vita tárgyát képezi az alacsonyabb szérum-1,25-dihidroxi-D 3 -vitamin-szint és a hepatocellularis carcinoma kialakulásának magasabb kockázata között fennálló ösz-szefüggés [24,25]. Huang és munkacsoportja a közel-…”
Section: Megbeszélésunclassified
“…An association has been established between low levels of vitamin D3 and several diseases including viral hepatitis and cancer development. Low serum levels of 25-OHD3 were proved to be associated with increased liver fibrosis in patients with non-alcoholic steatohepatitis [4] and type 2 diabetes mellitus [5] and reported to be associated with high risk of HCC development [6]. Moreover, the serum level of 25-OHD3 had been reported to affect the natural course and treatment response of chronic hepatitis C [7].…”
Section: Introductionmentioning
confidence: 99%
“…Results of the EPIC trial revealed that higher baseline levels of 25(OH)D are associated with a lower risk of HCC (per 10 nmol/l increase IRR 0.80; 95% CI 0.68-0.94) [48] . In contrast, dietary calcium, vitamin D, fat and protein from dairy sources are associated with increased HCC risk while the same nutrients from nondairy sources show inverse or null associations [49] .…”
Section: Vitamin Dmentioning
confidence: 99%